The role of PSMC4 in non-small cell lung cancer: implications for prognosis, diagnosis, and immune microenvironment modulation - Zhu, Lili; Li, Yuanjun; Xu, Yunfei; Lei, Jian (Frontiers in Oncology, 2025)
IntroductionNon-small cell lung cancer (NSCLC) remains a principal cause of cancer-related mortality. The discovery of novel biomarkers is pivotal for enhancing early diagnosis, refining prognostic evaluations, and optimizing targeted therapeutic strategies. Proteasome 26S subunit ATPase 4 (PSMC4), a proteasome subunit essential for protein degradation, influences tumor progression regulatory mechanisms. Despite its recognized importance, the specific contributions of PSMC4 to NSCLC progression are not well defined.MethodsThis investigation employs a combination of bioinformatics and histological methods to delineate the expression profile of PSMC4 in NSCLC and its correlations with clinicopathological characteristics, diagnostic efficacy, prognostic value, and tumor microenvironment.ResultsWe reveal an elevated level of PSMC4 in various malignancies, notably lung adenocarcinoma. Elevated levels of PSMC4 are strongly associated with higher pathological T stages, N stages, and pathological stages. Analysis using receiver operating characteristic curves demonstrates the high diagnostic sensitivity and specificity of PSMC4. Furthermore, patients with elevated PSMC4 levels experience markedly reduced overall survival, disease-specific survival, and progression-free intervals. Both univariate and multivariate Cox regression analyses substantiate that PSMC4 serves as an independent prognostic marker. Analysis of differentially expressed genes and functional annotation demonstrate that genes related to PSMC4 are crucial across a spectrum of biological processes, including DNA replication, chromatin assembly, and mitotic prophase. Gene set enrichment analysis reveals significant correlations between PSMC4 and essential signaling pathways such as the G2/M DNA damage checkpoint, WNT signaling pathway, and cellular senescence. Moreover, immunohistochemical evaluations confirm the increased expression of PSMC4 in NSCLC tissues. Functional assays reveal that PSMC4 accelerates the proliferation of lung cancer cells and tumor growth in xenograft models.DiscussionThese results highlight the potential of PSMC4 as a diagnostic and prognostic marker in NSCLC and elucidate its integral role within the tumor immune microenvironment. Consequently, targeting PSMC4 emerges as a viable therapeutic approach for NSCLC.